Sugar Consumption Produces Effects Similar to Early Life Stress Exposure on Hippocampal Markers of Neurogenesis and Stress Response - Maniam, Jayanthi; Antoniadis, Christopher P.; Youngson, Neil A.; Sinha, Jitendra K.; Morris, Margaret J. (Frontiers in Molecular Neuroscience, 2016)
Adverse early life experience is a known risk factor for psychiatric disorders. It is also known that stress influences food preference. We were interested in exploring whether the choice of diet following early life stress exerts long-lasting molecular changes in the brain, particularly the hippocampus, a region critically involved in stress regulation and behavioural outcomes. Here, we examined the impact of early life stress induced by limited nesting material (LN) and chronic sucrose availability post-weaning on an array of hippocampal genes related to plasticity, neurogenesis, stress and inflammatory responses and mitochondrial biogenesis. To examine mechanisms underlying the impact of LN and sugar intake on hippocampal gene expression, we investigated the role of DNA methylation. As females are more likely to experience adverse life events, we studied female Sprague-Dawley rats. After mating LN was imposed from days 2-9 postpartum. From 3-15 weeks of age, female Control and LN siblings had unlimited to access to either chow and water, or chow, water and 25% sucrose solution. LN markedly reduced glucocorticoid receptor (GR) and neurogenic differentiation 1 (Neurod1) mRNA, markers involved in stress and hippocampal plasticity respectively, by more than 40%, with a similar effect of sugar intake in control rats. However, no further impact was observed in LN rats consuming sugar. Hippocampal Akt3 mRNA expression was similarly affected by LN and sucrose consumption. Interestingly, DNA methylation across 4 CpG sites of the GR and Neurod1 promoters was similar in LN and control rats. In summary, early life stress and post-weaning sugar intake produced long-term effects on hippocampal GR and Neurod1 expression. Moreover we found no evidence of altered promoter DNA methylation. We demonstrate for the first time that chronic sucrose consumption alone produces similar detrimental effects on the expression of hippocampal genes as LN exposure.